2013
DOI: 10.4236/ojfd.2013.32010
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian Formulation for Water Wave Equation

Abstract: This paper concerns the development and application of the Hamiltonian function which is the sum of kinetic energy and potential energy of the system. Two dimensional water wave equations for irrotational, incompressible, inviscid fluid have been constructed in cartesian coordinates and also in cylindrical coordinates. Then Lagrangian function within a certain flow region is expanded under the assumption that the dispersion μ and the nonlinearity ε satisfied   2 O   . Using Hamilton's principle for water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Potential energy is related to the fluid pressure in the pipeline. Sultana & Rahman (2013) [18] indicated that these forms of energy involve a function that represents the energy associated with leaks. This function captures the effect of leaks on the system and can vary depending on the location and magnitude of the leaks and is used to model and quantify the hydraulic head loss owing to leaks in the pipeline.…”
Section: Hamiltonian Conservative Systemmentioning
confidence: 99%
“…Potential energy is related to the fluid pressure in the pipeline. Sultana & Rahman (2013) [18] indicated that these forms of energy involve a function that represents the energy associated with leaks. This function captures the effect of leaks on the system and can vary depending on the location and magnitude of the leaks and is used to model and quantify the hydraulic head loss owing to leaks in the pipeline.…”
Section: Hamiltonian Conservative Systemmentioning
confidence: 99%
“…The shallow water equations (SWE) describe the kinematic behaviour of a thin inviscid single fluid layer flowing over a variable topography. In the setting of irrotational flows and flat bottom topography, the fluid is described by a scalar potential ϕ and the canonical Hamiltonian formulation (29) is recovered [37]. The resulting Algorithm 3 Rank-adaptive reduced basis method…”
Section: Shallow Water Equationsmentioning
confidence: 99%
“…The shallow water equations (SWE) describe the kinematic behaviour of a thin inviscid single fluid layer flowing over a variable topography. In the setting of irrotational flows and flat bottom topography, the fluid is described by a scalar potential φ and the canonical Hamiltonian formulation (8.1) is recovered [34]. The resulting time-dependent nonlinear system of PDEs is defined as…”
Section: Shallow Water Equationsmentioning
confidence: 99%